Evaluation of carbon capture potential and soil analysis of a Brachiaria brizantha pasture system at two altitudes in the department of Cauca, Colombia (2013)
The upper sub-basin of the Las Piedras river, located northeast of Popayan on the western flank of the central mountain range, supplies water to the city of Popayán, directing its water resource to the "El Tablazo" water treatment plant. In the Las Piedras region, local communities are engaged in livestock frontier expansion processes that have a detrimental effect on water quality. Use of better quality grasses could reduce the need for expansion. This study in the Arrayanales microbasin of the river sought to determine the level of carbon capture by Toledo grass (Brachiaria brizantha) by the inventory method, identifying the photosynthetic growth rate at the aerial and root levels, as well as total carbon analysis using the COT method. The research was carried out at an altitude of approximately 2.600 m.a.s.l. and coordinates 76 ° 31 '10 "West and 2 ° 21' 45" North. Physical and chemical properties of the soils were also determined in the Agrochemical Laboratory of the University of Cauca, while bromatological analysis was carried out on the grass under study to assess the nutritional quality. It was found that in Arrayanales, the carbon capture level is lower than that found in Popayan; these levels are consistent with the data obtained from the analysis of total organic carbon. The photosynthetic growth rate is higher in Popayan because the environmental conditions of temperature, altitude, humidity, and precipitation rate, etc., favor grass growth. The soils of this region are allophanic in origin. They showed a low pH and an intermediate level of macro and micronutrients. This favors their potential use for diverse crops, i.e. using this soil resource for activities other than livestock.